Gender differences in salivary hormones and perception of exertion of elite volleyball players during tournament - Penailillo, L.; Escanilla, F.; Jury, E.; Castro-Sepulveda, M.; Zbinden-Foncea, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Sports tournaments induce both physiological and psychosocial stress, which seems to be different between men and women (1). It induces anticipatory rises in testosterone and cortisol hormones, which may affect performance and perceived exertion. The aim of this study was to compare the changes in salivary cortisol and testosterone concentrations between men and women during an official volleyball tournament and to correlate the changes in these hormones with the perceived exertion after match. Methods: Three matches of each team were assessed in the group stage of the Men and Women South American Volleyball Championship. Measures of salivary cortisol and testosterone were taken in fasting state, before and after each match (2). The rate of perceived exertion (RPE) was assessed after each match. Changes in these variables were compared between men and women and between matches with a multifactorial ANOVA. Results Fasting cortisol concentrations were higher in women than men and fasting testosterone was higher in men than women. Women did not increase their cortisol concentrations after any match. However, cortisol concentration increased after the second match. The average rate of perceived exertion was correlated with the average change in testosterone level after the matches in both women and men, which was not observed for cortisol concentration. Discussion: These results suggest that women have more pronounced anticipatory responses and increase their hormonal levels less throughout tournaments than men. It seems that hormone changes in men are modulated by the experience in this type of competition and the opponent´s level.